2020
DOI: 10.1016/j.artd.2020.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty for Developmental Dysplasia of Hip vs Osteoarthritis: A Propensity Matched Pair Analysis

Abstract: Background: The purpose of this study was to use the American College of Surgeons National Surgical Quality Improvement Program to compare the perioperative and postoperative outcomes after total hip arthroplasty (THA) for DDH and primary OA via a propensity-matched pair analysis and the valuation of THA between both groups. Material and Methods: All patients who underwent THA between 2008 and 2016 were identified from National Surgical Quality Improvement Program database via the current procedural terminolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
(62 reference statements)
0
15
0
1
Order By: Relevance
“…As prior studies have demonstrated higher rates of aseptic loosening and acetabular component revision when cups are placed outside of the true hip center [ [9] , [10] , [11] ], this is especially important for THA in dysplastic hips. Patients with hip dysplasia requiring THA are often younger, have higher functional demands, and lower overall implant survival than patients with primary osteoarthritis [ [12] , [13] , [14] ]. Maximizing implant longevity is therefore critical when approaching these cases, and from a biomechanical perspective, data support inferomedial cup placement [ [9] , [10] , [11] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As prior studies have demonstrated higher rates of aseptic loosening and acetabular component revision when cups are placed outside of the true hip center [ [9] , [10] , [11] ], this is especially important for THA in dysplastic hips. Patients with hip dysplasia requiring THA are often younger, have higher functional demands, and lower overall implant survival than patients with primary osteoarthritis [ [12] , [13] , [14] ]. Maximizing implant longevity is therefore critical when approaching these cases, and from a biomechanical perspective, data support inferomedial cup placement [ [9] , [10] , [11] ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these strategies, however, come at the expense of hip biomechanics [ 8 ], acetabular bone stock, and/or can be associated with high rates of component loosening [ [9] , [10] , [11] ]. As patients with hip dysplasia are often younger with a greater functional demand and higher revision rates than patients with primary osteoarthritis [ [12] , [13] , [14] ], optimizing implant longevity, hip biomechanics, and acetabular bone stock is arguably more important for these patients. The use of bulk femoral head autograft (FHA) allows for re-establishment of the true hip center and has the advantage of augmenting bone stock for possible future revisions although its use has historically been controversial due to long-term concerns of graft resorption ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“… 5 - 7 However, recent reports showed that complication rates were similar between non-DDH and DDH patients. 37 , 38 Siddiqi et al 38 demonstrated that no statistically significant differences were found in readmission or reoperation rates between non-DDH and DDH patients. In this study, postoperative complications, such as infection, dislocation, and nerve paralysis, did not occur until one year of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…THA for secondary arthritis has been reported to be associated with longer operative duration, transfusion rates, hospital length of stay, intraoperative, and postoperative complications. [10][11][12][13] Meticulous planning and surgical technique may be enhanced by technology assistance to improve accuracy and mitigate complications. Therefore, the purpose of this case report was to demonstrate the utility and efficacy of robotic-arm technology in complex primary THA.…”
mentioning
confidence: 99%